2023
DOI: 10.7554/elife.88210
|View full text |Cite
|
Sign up to set email alerts
|

A critical evaluation of protein kinase regulation by activation loop autophosphorylation

Abstract: Phosphorylation of proteins is a ubiquitous mechanism of regulating their function, localization, or activity. Protein kinases, enzymes that use ATP to phosphorylate protein substrates are, therefore, powerful signal transducers in eukaryotic cells. The mechanism of phosphoryl-transfer is universally conserved among protein kinases, which necessitates the tight regulation of kinase activity for the orchestration of cellular processes with high spatial and temporal fidelity. In response to a stimulus, many kina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 167 publications
(249 reference statements)
0
13
0
Order By: Relevance
“…In all kinases, substrate recognition and catalysis are dependent on three residues a Lys (part of a stable β sheet in the N-lobe), a Glu, and an Asp located in the C-lobe. 43 The Lys residue coordinates the binding of ATP, while Glu and Asp bind magnesium ions and coordinate two arginine residues at position P-3 and P-5 in the substrate. 43 These residues are conserved in LjSK1 90−467 as Lys167, Glu179, and Asp263.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In all kinases, substrate recognition and catalysis are dependent on three residues a Lys (part of a stable β sheet in the N-lobe), a Glu, and an Asp located in the C-lobe. 43 The Lys residue coordinates the binding of ATP, while Glu and Asp bind magnesium ions and coordinate two arginine residues at position P-3 and P-5 in the substrate. 43 These residues are conserved in LjSK1 90−467 as Lys167, Glu179, and Asp263.…”
Section: Resultsmentioning
confidence: 99%
“…43 The Lys residue coordinates the binding of ATP, while Glu and Asp bind magnesium ions and coordinate two arginine residues at position P-3 and P-5 in the substrate. 43 These residues are conserved in LjSK1 90−467 as Lys167, Glu179, and Asp263. 9 Lys167 forms a hydrogen bond with Glu179, while the side chain of Asp263 forms a hydrogen bond to the main chain nitrogen of Ser301 like in the mammalian GSK3β 41 (Figure 5).…”
Section: Resultsmentioning
confidence: 99%
“…Instead, ATP was the only high-energy phosphoryl donor that promoted the formation of ppS76-NAGK, and the conversion was proportional to ATP concentration. Inspection of the crystal structure of wt-NAGK, into which we modeled a phosphoserine side chain at S76, illustrates how the γ-phosphoryl group of ATP and pS76 are within 3.4 Å of each other, suggesting that an intramolecular phosphoryl transfer is well possible (Figure b) …”
Section: Discussionmentioning
confidence: 99%
“…Inspection of the crystal structure of wt-NAGK, into which we modeled a phosphoserine side chain at S76, illustrates how the γphosphoryl group of ATP and pS76 are within 3.4 Å of each other, suggesting that an intramolecular phosphoryl transfer is well possible (Figure 7b). 49 The initial phosphorylation on S76 can be catalyzed by the protein kinase AurB. Pyrophosphorylation thereafter is facilitated by the presence of ATP.…”
Section: ■ Discussionmentioning
confidence: 99%
“…While these approaches can be highly effective in favorable cases, they are still of limited general applicability because the kinases responsible for the vast majority of human phosphoylation sites are unknown, although ongoing efforts to characterize the substrate specificities of broad selections of kinases are extending the utility of these approaches. A further limitation is that even for many cases in which the relevant kinase is known, obtaining an active form of the kinase for in cell or in vitro use is not trivial, because its activation involves regulatory mechanisms such as autophosphorylation, phosphorylation by another kinase, or interaction with activator proteins. , Recent evidence has also shown that specificity of kinases can change depending activation status and that the broad substrate specificity of many kinases can result in multiple off-target sites being inadvertently phosphorylated on a given substrate protein. Consequently, generating site-specifically phosphorylated proteins using kinases, without modifications to other sites in the protein (e.g., Ser/Thr to Ala to prevent off-target phosphorylation) is challenging at best, and often unfeasible.…”
Section: Introductionmentioning
confidence: 99%